Simplified method of forecasting the influence of cooling intensity during hardening on the mechanical properties of steel products - Deyneko, Leonid; Kobasko, Nikolai (Technology audit and production reserves, 2020)
The object of research is the structure and mechanical properties of steel at the central points of hardened products. In this work, a technique has been developed based on comparing the cooling rate in the central region of the product with the cooling rate of a test sample with a diameter of 5–6 mm, investigated in laboratory conditions. By this time, this approach was not possible, since two main problems had not been resolved. The transition from a small sample to a real product during quenching was scientifically unreasonable due to the great complexity of the problem. There were no known mathematical relationships for calculating the cooling rate when quenching products of arbitrary shape in liquids. Recently, these problems have been solved and steel with optimal hardenability has appeared, which can be cooled very quickly. This simplified the solution to this problem. The technique developed in this work helps to temper metal products in such a way that there are large compressive residual stresses on the surface, and in the middle there is a bainite structure of high strength and increased toughness. This allows to increase the service life of hardened products, reduce the percentage of alloying elements, and also maintain a clean environment. In this regard, based on the achievements of science in recent decades, a method is proposed for predicting the structure and mechanical properties of steel during quenching of real parts. This technique can be used to increase the durability of machine parts and tools. The work also notes the prospects of using aqueous solutions of low-concentration polymers for intensive hardening of steel products. In this case, when simulating the cooling rate during quenching of real products, test samples are quenched in aqueous solutions of the same polymers of increased concentration in order to form a stable vapor film. The stable vapor film ensures a stable heat transfer coefficient. This increases the accuracy of modeling and expands the capabilities of the proposed calculation method.